NABI IBRAHIM DAN PENDIDIKAN SELESTIAL: MENDIDIK SEPERTI CARA TUHAN MENYIAPKAN NABINYA - Jumatriadi Jumatriadi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2018)
Prophet Ibrahim is including the Father of the Prophets and Apostles, he educates as the way God educates His prophet. The pattern of education that he applied could be said as celestial education. Celestial education is education that is closely related to Allah (divinity), where the prophets are obliged to educate humans and provide understanding to them. This celestial education moves along with the soul of humanity, so dwell in the soul of fear and hope, fear of Allah SWT and His punishment, hoping for His mercy, His pleasure, and the hope of getting a reward from Him. Celestial education built by Prophet Ibrahim as, can be seen from three approaches, namely: (1) education is seen as developing potential; (2) education is seen as cultural inheritance; and (3) education is seen as an intraction between the development of potential and cultural inheritance. The methods of celestial education applied by the prophet Ibrahim as is the method of exemplary or uswatun hasanah, method of advice, method of dialogue, and method of fighting arguments. Education requires facilities for smoothness and success of the educational process so that the expected results are achieved. Among the facilities used by Prophet Ibrahim as in the concept of education are baitullah, antariksah, and animals. The application of celestial education in the current era of globalization is very important to direct the growth and development of children with all the potential that Allah bestowed upon him to be able to develop the mandate and responsibility as the vicegerent of Allah SWT on earth to serve Him.